The Commercial Dimension Of The Ports Of The Province Of Skikda: Historical Context And Current Port Activity - Lydia, Bouchama (Migration Letters, 2024)
As visualized nowadays, the City of Skikda is the result of a radical urbanization process that evolved from the core of a Phoenician commercial port to a port pole. Besides, its historical context makes clear the emergence of three ports that arose through successive time stations that had an impact on the development of the port function of the city, in which there were numerous activities, specialization and spheres of influence. However, the paper dealt with a brief presentation on the commercial role played by the ports of Skikda through the ages, together with discussing the current reality of ports in terms of classification thereof according to their economic activity, their capacities, the quantity of cargo, the number of imported containers and incoming ships, along with addressing the issue of the port function of the city and globalization, as well.